Urgensi Pembelajaran Nilai Berbasis Sosial Media untuk Menumbuhkan Keadaban Kewarganegaraan - Zulkifli; Yoga Gandara (Jurnal Educatio FKIP UNMA, 2021)
This research is motivated by the shift in learning practices and students' interest in learning to become a concern and focus in developing the learning process. The young generation (millennials) of course currently have social media accounts, this can be used by teachers as learning media in schools. In order to control the attitudes and behavior of students in using social media, teachers can use it through extracting the meaning of values ​​from the social media content. This research uses qualitative methods and literature research analysis. The results of the study indicate that with the development of information and communication technology, especially the development of social media, it is deemed necessary to innovate social media-based value learning models to foster civil civilization in civic education. Value-based social media learning will be reflected in the characteristics of reflective learning, communication and teamwork skills, individual and group creativity in groups, and will have a positive value impact for individuals and groups when exploring the value of group discussion topics. adoption of social media should be included as part of the school teaching and learning curriculum, and can only be done after an in-depth and thorough analysis with clear guidelines relating to the use of these tools should be provided for both teachers and students should be given clear guidance on the use of these tools , and information on the use of these tools should be provided. Learning activities that use various social media tools must also cover all aspects to support inclusive students from different learning styles. Most importantly, learning activities designed by educators and promoted through social media must be based on good teaching and learning theories to generate interest and learning experiences.